2015
DOI: 10.1177/0363546514563282
|View full text |Cite
|
Sign up to set email alerts
|

Sports Participation 2 Years After Anterior Cruciate Ligament Reconstruction in Athletes Who Had Not Returned to Sport at 1 Year

Abstract: Most athletes who were not playing sport at 1 year had returned to some form of sport within 2 years after ACL reconstruction, which may suggest that athletes can take longer than the clinically expected time of 1 year to return to sport. However, only 2 of every 5 athletes were playing their preinjury level of sport at 2 years after surgery. When the results of the current study were combined with the results of athletes who had returned to sport at 1 year, the overall rate of return to the preinjury level sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
190
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(206 citation statements)
references
References 39 publications
15
190
1
Order By: Relevance
“…A number of studies have found associations between return to sports and psychosocial/psychological variables (kinesiophobia/fear of reinjury, knee-related self-efficacy, confidence). 2,4,5,15,22,35,36 Further evaluation of the impact of these factors, along with that of strength, function, and performance, on return to sports is warranted. Third, only one criterion value (90%) was evaluated in this study, based on what is commonly regarded as acceptable for return-to-sport participation after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found associations between return to sports and psychosocial/psychological variables (kinesiophobia/fear of reinjury, knee-related self-efficacy, confidence). 2,4,5,15,22,35,36 Further evaluation of the impact of these factors, along with that of strength, function, and performance, on return to sports is warranted. Third, only one criterion value (90%) was evaluated in this study, based on what is commonly regarded as acceptable for return-to-sport participation after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the discordance between patient satisfaction and returning to the pre-injury activity may suggest that imposing a generic definition of successful outcome may be difficult; that success is better defined by the individual. Recent studies have highlighted the potential impact of contextual factors (including social and lifestyle-related factors) on returning to the pre-injury sport, [32][33][34][35][36] and that many people do not return to their pre-injury sport following surgery. 32 People choose to participate or cease participating for many reasons that may have nothing to do with their knee.…”
Section: Discussionmentioning
confidence: 99%
“…When the level of sport participation was taken into account, only 65% returned to their preinjury level of sport and 55% returned to competitive sport, despite achieving successful surgical outcomes. [9][10][11][12][13] Readiness to return to sport after ACLR is commonly based on a multitude of functional measures, such as strength, power, and proprioception of the involved extremity. 4,6 Successful functional outcomes and satisfactory patient-reported outcomes are often the main criteria for clearance in returning an athlete to sport and the preinjury level of activity after ACLR.…”
mentioning
confidence: 99%